Transcriptomics and trans-organellar complementation reveal limited signaling of 12-cis-oxo-phytodienoic acid during early wound response in Arabidopsis - Khansa Mekkaoui; Ranjit Baral; Fiona Smith; Moritz Klein; Ivo Feussner; Bettina Hause (Nature Communications)
Abstract 12-cis-oxo-phytodienoic acid (OPDA), a precursor of jasmonoyl-isoleucine (JA-Ile), is known to have distinct signaling roles in Arabidopsis, as shown in studies using the opr3 mutant, which lacks OPDA REDUCTASE3 (OPR3). This mutant, however, accumulates low levels of JA-Ile through an OPR2-mediated bypass. To investigate OPDA signaling, the wound-induced transcriptome of the opr2opr3 mutant is compared to that of wild-type and allene oxide synthase mutant. Endogenous OPDA shows no unique transcriptional signature under control or wounding conditions, and previously identified OPDA-responsive genes are wound-induced independently of OPDA. Applying OPDA to opr2opr3 triggers a distinct response suggesting compartmentalization of endogenously formed OPDA. Trans-organellar complementation reveals that expression of OPR3 or OPR2 in opr2opr3 restores JA-Ile production regardless of localization, whereas mitochondrial targeted OPR1 exhibiting low OPDA/4,5-ddh-JA conversion activity does not. Our findings show that OPDA primarily serves as a JA precursor with limited independent signaling functions in the early wound response.